KARAKTERISASI TANAH PUTIH DARI KABUPATEN MALUKU TENGGARA MENGGUNAKAN XRF DAN XRD - Victor Kayadoe (Molluca Journal of Chemistry Education (MJoCE), 2021)
The use of white soil in various applications is very dependent on its composition and purity. Thus, this material needs to be characterized to determine the suitability of its application in a field. In this study, white soil was characterized using XRF to determine the elemental composition and XRD to determine the purity of the mineral phase in the material. The results of characterization using XRF showed that all white soil samples were dominated by calcium, namely 97.15% with small amounts of other elements. While the results of characterization using XRD showed that white soil was dominated by the calcite phase (CaCO3), with the highest peak at the diffraction angle of 29.4753o with a relative intensity of 100%.